2007
DOI: 10.1001/archfaci.9.6.400
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Definitive In-Theater Repair of Facial Fractures

Abstract: Definitive repair of facial fractures with ORIF on American military personnel in theater is advised when the aforementioned criteria are observed. An otolaryngologist is a crucial member of the head and neck trauma team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…14,15 In the Balkans, conflict wounds became infected postoperatively in 19% of war-wounded patients, 16 and in the Iran-Iraq war, 11% of maxillofacial injuries were complicated by infection. 17 Two small case series from the Iraq war of patients undergoing open reduction and internal fixation of fractures at Role 3 (e.g., combat support hospital) described a 0% infection rate among 17 patients; 18 however, a second review of 130 patients described a 24% infection rate. 19 Actual pathogen descriptions of maxillofacial infections in combat-associated wounds are limited and include Klebsiella spp., and fungi (likely Candida spp.…”
Section: Maxillofacial and Neck Injuriesmentioning
confidence: 99%
“…14,15 In the Balkans, conflict wounds became infected postoperatively in 19% of war-wounded patients, 16 and in the Iran-Iraq war, 11% of maxillofacial injuries were complicated by infection. 17 Two small case series from the Iraq war of patients undergoing open reduction and internal fixation of fractures at Role 3 (e.g., combat support hospital) described a 0% infection rate among 17 patients; 18 however, a second review of 130 patients described a 24% infection rate. 19 Actual pathogen descriptions of maxillofacial infections in combat-associated wounds are limited and include Klebsiella spp., and fungi (likely Candida spp.…”
Section: Maxillofacial and Neck Injuriesmentioning
confidence: 99%
“…16 A recent review of the repair of facial fractures in a military setting has shown that in-theater open reduction and internal fixation of facial fractures is possible and safe. 17 Once again, the plastic surgeon's expertise and familiarity with facial trauma management can be advantageous for optimal repair of these complex soft-tissue and bony injuries. If facial fractures are suspected in a given patient, definitive diagnosis is routinely made with the aid of a computed tomographic scan, when available.…”
Section: Facial Traumamentioning
confidence: 99%
“…44 -46 However, up to 61% sustain head/neck injury, and approximately 70% suffer extremity injury according to some reports. 1,45,47 Just as military and civilian neurologists hope to gain insight from the large number of closed head injuries in OIF, reconstructive surgeons have the opportunity to help redeem losses through clinical advancements. 44 -46,48 -50 Some areas have been revisited.…”
Section: The Global War On Terrorismmentioning
confidence: 99%
“…The debate for surgery in-theater or at home has been discussed in both World Wars and in recent conflict, partially due to the high rates of Acinetobacter baumannii infection in OIF casualties. 45 Similarly, the composition of multidisciplinary maxillofacial surgery teams continues to be contended. 11,45 Hand surgery is also a shared field, and although designated hand centers do not currently exist in the military like in WWII and Vietnam, modern fellowship training has resulted in outstanding care.…”
Section: The Global War On Terrorismmentioning
confidence: 99%
See 1 more Smart Citation